2019
DOI: 10.1080/16549716.2019.1638020
|View full text |Cite
|
Sign up to set email alerts
|

Stunting and severe stunting among infants in India: the role of delayed introduction of complementary foods and community and household factors

Abstract: Background: Delayed introduction of solid, semi-solid or soft foods (complementary feeding) and associated factors are related to stunting and severe stunting among children in many low-and middle-income countries. In India, however, there is limited evidence on the relationship between delayed complementary feeding and associated factors with stunting and severe stunting to advocate for policy interventions. Objectives: The present study investigated the relationship between delayed complementary feeding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 49 publications
10
40
0
8
Order By: Relevance
“…This low rate of EBF indicates that a substantial proportion of newborns in ECOWAS countries are fed with water and/or prelacteal foods before the age of at least six months. This will, in turn, predispose the infant to gastrointestinal infections due to intake of contaminated prelacteal [18] or complementary foods [1,3,19]. In a recent study conducted in Nigeria, one of the ECOWAS countries with the largest population and economy [10], an estimated 22,371 diarrhoea-related deaths among children under five years could have been averted in 2016 if nursing mothers had strictly adhered to appropriate breastfeeding practices, particularly EBF [20].…”
Section: Introductionmentioning
confidence: 99%
“…This low rate of EBF indicates that a substantial proportion of newborns in ECOWAS countries are fed with water and/or prelacteal foods before the age of at least six months. This will, in turn, predispose the infant to gastrointestinal infections due to intake of contaminated prelacteal [18] or complementary foods [1,3,19]. In a recent study conducted in Nigeria, one of the ECOWAS countries with the largest population and economy [10], an estimated 22,371 diarrhoea-related deaths among children under five years could have been averted in 2016 if nursing mothers had strictly adhered to appropriate breastfeeding practices, particularly EBF [20].…”
Section: Introductionmentioning
confidence: 99%
“…Study based in India showed that maternal age is positively associated with stunting among children (58), while some studies showed that stunting is inversely related with maternal age (63,64). Many studies have documented that with the increase of maternal education, the chances of stunting decrease among children (44,54,(65)(66)(67)(68). Mother's body mass index that is negatively associated with stunting among children, also another important risk factor of stunting among children as evidenced by the previous studies (28,44,67).…”
Section: Review Of the Literaturementioning
confidence: 95%
“…It has also been observed that household characteristics, e.g. religion, caste or social groups (44,65), wealth index and the place of residence (72,73) are also associated factors of stunting among children. Besides these, studies evaluated the effects of ICDS at the national level in India shows that there are no signi cant effects on reducing stunting among children who are accessing the services from ICDS (74-76).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Birth weight and household wealth index are reported to be negatively related to both stunting and wasting. Other common predictors for stunting were low maternal height, low maternal BMI, low frequency of antenatal care visits, higher birth order, low maternal educational level, children of mothers without decision making power regarding food, lack of minimum meal frequency, no feeding of eggs, dairy products, fruits and/or vegetables, or the delayed introduction of complementary foods, increasing age of child, and households without access to improved sanitation [139], [143], [144], [145], [146]. Acute respiratory infection was predictive for underweight, whereas diarrhea was a major driver for stunting among Indian children below five years [147].…”
Section: Relationship Between Linear Growth and Wasting As Well As Imentioning
confidence: 99%